Classification of polyethylene cling films by attenuated total reflectance-Fourier transform infrared spectroscopy and chemometrics - Telford, C.; Burrows, B.; Sauzier, G.; Van Bronswijk, W.; Houck, M.; Maric, M.; Lewis, Simon (R S C Publications, 2017)
Attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) was utilised to analyse nine differently branded cling films. Principal component analysis (PCA) was used to assess the intra-sample variability, i.e. the variation within individual cling film rolls; as well as the inter-sample variability, which explores the variability between different rolls of cling film. Linear discriminant analysis (LDA) was then employed to develop a predictive classification model which gave 100% correct differentiation between three brand groupings of cling film, and accurately classified all of the validation samples obtained from different rolls from the same manufacturers.